Maintaining Medical Professionalism: Promoting Balance and Preventing Student Burnout - Winona Lee (MedEdPORTAL, 2014)
Abstract Student burnout is a significant issue to trainees in the health professions, and is particularly pertinent to pre-medical and medical students early in their training. Awareness of student burnout and its impact on future health care providers and their patients is a critical aspect of medical education. This presentation was created to introduce ‘Imi Ho‘ōla post-baccalaureate students to the topic of student burnout and to educate them on the importance of creating a sense of balance between their academic and personal lives. It is taught as one component of a larger medical professionalism and ethics curriculum which was implemented in 2007, and has remained a component of this curriculum since. This presentation offers medical education training programs the opportunity for student reflection and open discussion regarding student burnout. Given preliminary evaluation results, the presentation has been positively received by students. The presentation has been modified, retaining its strengths and addressing its weaknesses, based on this feedback as well as current literature. Although the presentation was created for post-baccalaureate students with a conditional acceptance to medical school, it can be replicated and utilized for medical students nationwide.